Topography and topology optimization of diesel engine components for light-weight design in the automotive industry - Yıldız, Ali Rıza; Kilicarpa, Ulas Aytac; Demirci, Emre; Dogan, Mesut (Carl Hanser Verlag, 2019)
This paper focuses on the optimal design of connecting rods and optimal design of a particle sensor system in diesel engines in order to save material, reduce costs and enhance quality. Optimization is very significant for developing better designs and means less material, lower costs and better conditions. Topology and topography optimization are new but likewise very important optimization approaches for the automotive industry. One of the aims of this study is to create an optimal design for connecting rod components and to use these components in diesel engines to comply with new emission regulations. An analysis of the connecting rods of an existing model was conducted using mathematical data obtained from numerical formulas in order to determine if the part was suitable for topology optimization. According to the results obtained from the topology optimization of the existing model, a new design was created. A comparison of the new design with the existing one showed that the mass of the model was reduced by 18%, while all product expectations were me. Another purpose of the study is to provide an optimal design for a particle sensor system and utilize this system in automobiles to achieve the new emission values required by Euro-Norm 6c regulations. Within the scope of this optimization study, a specific particle measurement system foreseen for Renault 1.5 dCi engines was considered and designed optimally. According to the output of the topology and topography optimization methods, the particle sensor system was designed optimally, and the mass of the system was reduced by 26.7%.
Keywords: Optimum design; topography optimization; topology optimization; diesel engine; weight reduction